Accessory mitral valve without subaortic obstruction of left ventricular outflow tract in a middle-aged male - Golias, Christos (BMJ Case Rep, 2012)
Accessory mitral valve (AMV) is a rare congenital abnormality with a usually early-age clinical onset, being potentially a cause of subvalvular obstruction of the left ventricular outflow tract. This report describes the case of a 60-year-old patient presented with palpitations and chest pain. Primary evaluation revealed a ventricular tachycardia episode while transthoracic echocardiography showed an intracardiac additional structure at the level of the left ventricular outflow tract. After transoesophageal echocardiography and paraclinical investigations this structure was proven to be an AMV tissue which did not provoke left ventricular outflow obstruction. This case presents an unusual late-age clinical onset of AMV without a clinically significant LVOT (left ventricular outflow tract) obstruction and highlights the importance of transthoracic and transoesophageal echocardiography in the diagnosis of this rare cardiological entity.